1979
DOI: 10.3109/01485017908985064
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine studies of azoospermia, II. Serum steroid levels in obstructive azoospermia

Abstract: Serum estrone, estradiol, estriol, progesterone, 17 a-hydroxyprogesterone, and testosterone were determined in the sera of 25 normal males and 25 patients with obstructive azoospermia. An increase in testosterone and estriol levels, and a decrease in other hormones were demonstrated in patients with obstructive azoospermia. These long-term effects of obstruction of the vas apparently also occur in comparable situations, for example, after vasectomy.Key Words: Azoosperrnia; Estrogens; Progesterones; Androgens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…(1999) describing activation of telomerase by 17β‐estradiol via direct and indirect effects on the hTERT promoter with consecutive up‐regulation of hTERT mRNA expression. It would thus be conceivable that the different oestrogen level found, for example, in patients with SCOS (Abdalla et al ., 1979) contribute to the reduced hTERT expression in telomerase positive cells of patients with spermatogenesis defects. It is also possible that, besides this some other endocrine factors that are important for spermatogenesis (Berruti, 1998), may also play a role in the regulation of hTERT expression.…”
Section: Discussionmentioning
confidence: 99%
“…(1999) describing activation of telomerase by 17β‐estradiol via direct and indirect effects on the hTERT promoter with consecutive up‐regulation of hTERT mRNA expression. It would thus be conceivable that the different oestrogen level found, for example, in patients with SCOS (Abdalla et al ., 1979) contribute to the reduced hTERT expression in telomerase positive cells of patients with spermatogenesis defects. It is also possible that, besides this some other endocrine factors that are important for spermatogenesis (Berruti, 1998), may also play a role in the regulation of hTERT expression.…”
Section: Discussionmentioning
confidence: 99%
“…The results are restricted to progesterone patterns in cases of obstructive azoospermia compared with fertile men. A significant decrease of progesterone in patients with obstructive azoospermia was found (Abdalla et al -1979). Purvis et al (1975) included the group of severe oligozoospermia to their investigations and found elevated progesterone levels in azoospermic and oligozoospermic men.…”
Section: Discussionmentioning
confidence: 98%
“…The few available clinical data about affections of plasma progesterone levels at impaired male fertility are contradictive and restricted to reports on azoospermia and oligozoospermia. Abdalla et al (1979) reported decreased levels or progesterone in 25 patients with obstructive azoospermia. Purvis et al (1975) found significantly higher plasma progesterone levels in eleven oligozoospermic and ten azoospermic men in comparison to a normozoospermic control group.…”
Section: Introductionmentioning
confidence: 99%